(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
A person’s personal and sexual identities both start to take shape during the adolescent years.The characteristics that are unique to adolescents, along with their immaturity, make it easier for them todevelop sexually risky behaviors, such as a lax attitude toward the use of barrier contraceptives or theconsumption of toxic substances, alcohol, or drugs during sexual activity an increase in sexuallytransmitted infections (STIs) and an increase in unintended pregnancies. One of the most effectivestrategies to discourage risky behaviors and encourage healthy and responsible sexuality is through thedissemination of information about sexual health through educational programmers. Every adolescenthas an interest in gaining additional knowledge regarding topics such as sexual activity, oneness,conception, pregnancy, birth control, and sexually transmitted diseases. In addition, they want to learnhow to accommodate sexuality within their own framework of values so that they can have the ability toform relationships that are both fulfilling and positive. The vast majority of young people, on the otherhand, have extremely limited access to knowledge and assistance on these topics. The provision ofaccurate information on topics connected to sexual behavior is something that health practitioners areable to and should do.